2021
DOI: 10.1108/itp-09-2019-0456
|View full text |Cite
|
Sign up to set email alerts
|

Gamified money: exploring the effectiveness of gamification in mobile payment adoption among the silver generation in China

Abstract: PurposeThis study investigates the use of gamification in promoting the silver generation's adoption of mobile payment technology through the gamified cultural practice of gifting red packets. It considers the effectiveness of using gamification in a cultural context to promote technology acceptance among older adults. This crossover between digital technology and cultural traditions brings unique gaming elements to the adoption of technology.Design/methodology/approachDrawing upon technology acceptance Model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 178 publications
(309 reference statements)
1
55
0
Order By: Relevance
“…Surprisingly, some articles did not show any effect (Makanyeza, 2017; Handarkho and Harjoseputro, 2020; Chaouali and Hedhli, 2019; Oliveira et al, 2014), while others indicate a significant relationship (Yu, 2012; Crabbe et al, 2009; Musa et al, 2015). Taking a different viewpoint, some researchers have investigated the moderating effect of social influence (Narteh et al, 2017), experience (Teo et al, 2015; Giovanis, Assimakopoulos, et al, 2019a), personality traits (Ha et al, 2012), e‐lifestyle (Yu, 2015), consumer involvement (Shankar et al, 2020), perceived security concerns (Jebarajakirthy and Shankar, 2021), perceived risk (Wong et al, 2021) to explain the mobile financial services adoption mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, some articles did not show any effect (Makanyeza, 2017; Handarkho and Harjoseputro, 2020; Chaouali and Hedhli, 2019; Oliveira et al, 2014), while others indicate a significant relationship (Yu, 2012; Crabbe et al, 2009; Musa et al, 2015). Taking a different viewpoint, some researchers have investigated the moderating effect of social influence (Narteh et al, 2017), experience (Teo et al, 2015; Giovanis, Assimakopoulos, et al, 2019a), personality traits (Ha et al, 2012), e‐lifestyle (Yu, 2015), consumer involvement (Shankar et al, 2020), perceived security concerns (Jebarajakirthy and Shankar, 2021), perceived risk (Wong et al, 2021) to explain the mobile financial services adoption mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from these, there are some theory‐specific antecedents that have been used seldom in the literature. These include the “task‐technology fit model” (Zhou et al, 2010; Oliveira et al, 2014; Baabdullah et al, 2019), “elaboration likelihood model” (Shankar et al, 2020), the concept of mindfulness (Flavian et al, 2020), “mood‐behaviour model and the affect infusion model” (Karimi and Liu, 2020), and “the prospect theory” (Wong et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic literature review from 2018 to 2021 on this subject area revealed that there were 119 articles published in academic journals listed on the SCOPUS database, 3 with 2019 and 2020 as the years with the most prolific number of publications (45%). Of these, about 60% (64 of the 119) were based on technology acceptance models, such as the Technology Acceptance Model (TAM), the Theory of Planned Behavior (TPB), the Unified Theory of Technology Acceptance and Use (UTAUT) for Unified Theory of Acceptance and Use of Technology) (Abdul Aziz et al 2020;Nur and Panggabean 2021;Malek et al 2017;Flavian et al 2020;Hee et al 2020;Liébana-Cabanillas et al 2018;Patil et al 2020;Wong et al 2021) -all of which were derived from the Theory of Reasoned Action (TRA) (Ajzen and Fishbein 1973;Fishbein and Ajzen 1975). Another 15% analyzed the use of applications for mobile payment from a perspective of various enablers or barriers (Cheng et al 2019;Zhang, Luximon, and Song 2019 In addition, nearly all were quantitative in nature, with the exception of Moghavvemi et al (2021), who used in-depth interviews to understand acceptance of mobile payments of merchants.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As yStats.com (2020) reports, only two-fifths (40%) of the population in Malaysia are interested in adopting e-wallets for purchases, payments and remittances. To facilitate e-wallet penetration, many service providers have integrated money gifts as an innovative feature to make their apps more entertaining and enjoyable (Wong et al, 2021). The money-gift function is an important digital gift-giving app because it can minimize a person's psychological and health risks during the pandemic while allowing users to exchange virtual blessings and preserve the spirit of celebration (The Straits Times, 2021).…”
Section: Introductionmentioning
confidence: 99%